Psychological actions for tactical thinking development on solving tasks in school volleyball - Hidalgo, Yanelis Quesada; Sánchez, José Ignacio Ruiz; Callejas, Taimí Wambrug; Sabates, Hilda Rosa Rabilero (International research journal of management, IT and social sciences, 2019)
The research aimed to design a proposal for psychological intervention actions that enable the development of tactical thinking in the solution of training and competition tasks, in school volleyball players of the EIDE “Cerro Pelado” of Camaguey For this purpose, it was based on the diagnosis of the individual features of consecutive thinking, flexibility, and speed, as well as the analysis of the decision-making process, in which the analysis and perception of the current defensive tactical game situation are related, with similar previous experiences to adopt the most appropriate solution, in athletes.